2005
DOI: 10.1007/s10086-005-0707-x
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols in Acacia mangium and Acacia auriculiformis heartwood with reference to heart rot susceptibility

Abstract: The heartwood of Acacia mangium is vulnerable to heart rot and this is the first study to investigate the role of heartwood extractives in its susceptibility. Acacia auriculiformis was compared with A. mangium because it is rarely associated with heart rot. The heartwood extracts of both species were dominated by three flavonoids (2,3-trans-3,4¢,7,8-tetrahydroxyflavanone, teracacidin, and 4¢,7,8,-trihydroxyflavanone), which were purified and identified by nuclear magnetic resonance spectroscopy. The latter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 14 publications
4
26
1
Order By: Relevance
“…The t R determined by LC-DAD analysis was also different: the unknown peak elutes at 14.4 min and taxifolin at 23.7 min. Barry et al (2005) found a peak with the same MS spectrum in extracts of acacia.…”
Section: Wood Typementioning
confidence: 76%
“…The t R determined by LC-DAD analysis was also different: the unknown peak elutes at 14.4 min and taxifolin at 23.7 min. Barry et al (2005) found a peak with the same MS spectrum in extracts of acacia.…”
Section: Wood Typementioning
confidence: 76%
“…Metabolites 7,4′-dihydroxyflavanone (3), 20) 6,7-dihydroxyflavanone (4), 21) 2′,4′-dihydroxychalcone (9), 22) 7,8-dihydroxyflavanone (10), 23) 7-hydroxy-4-cis-ol (15), 18) 4,2′,4′-trihydroxychalcone (16), 24) 7,3′,4′-trihydroxy-flavanone (17), 25) 7,3′,4′-trihydroxy-6-methoxyflavanone (19) 26) and 7,8,4′-trihydroxy-flavanone (20), 27) were identified by comparison with published data. Metabolite 15 was reported earlier as a microbial metabolite of 7-hydroxyflavanone by (Kostrzew-Suslow et al).…”
Section: Resultsmentioning
confidence: 99%
“…2005). Acacia auriculiformis has ca twofold extractive yield compared with A. mangium ( Barry et al. 2005) and heartrot incidence is much less in the former species ( Ito 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of 2,3‐ trans ‐3,4′,7,8‐tetrahydroxyflavanone (compound I) was determined from the same HPLC runs used for the BSA assay above. Peak areas were measured at 280 nm and quantified via comparison with an external standard of purified compound I ( Barry et al. 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation